Peningkatan Hasil Belajar IPS Materi Mobilitas Sosial Melalui Model Pembelajaran Example Non Example - Ifah Fachrul Hudzaifah (Peneliti.net, 2022)
Basically the purpose of social studies education is to educate and provide students with the basic skills to develop themselves according to their talents, interests, abilities and skills. The purpose of this research is to improve social studies learning outcomes through the example no example learning model. This type of research is Classroom Action Research (CAR). The analysis uses quantitative analysis, both for improving the quality of the learning process and social studies learning outcomes. The results of the study show that social studies learning has not been carried out properly. This can be seen from the learning activities which are still dominated by the teacher. The teacher is fixated on the material presented, namely what is in the handbook while students only have LKS from the publisher as a handbook, not supported by learning media, the teaching style is very monotonous, the teacher uses the lecture method and occasionally asks all students and students answer with simultaneously. However, after being given action through the example non-example learning mode, the average achievement showed a clear increase from 59.23 in the first cycle to 69.61 in the second cycle. Meanwhile, from the achievement of student learning completeness, there was also an increase from 61.54% in the first cycle and showed that learning had not been completed to 89.74% of students had completed it in the second cycle and showed that learning had been completed.